2013
DOI: 10.2152/jmi.60.1
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic fat deposition and global cardiometabolic risk: New paradigm in cardiovascular medicine

Abstract: The obesity epidemic is a global public health concern that increases the likelihood of morbidity and mortality of metabolic and cardiovascular disease (CVD) and threatens to reduce life expectancy around the world. The concept of the metabolic syndrome (MetS) takes into account that visceral fat plays an essential role in the development of metabolic and cardiovascular diseases. However, MetS cannot be used to assess global CVD risk but is at best one more modifiable CVD risk factor. Thus, global cardiometabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 81 publications
(87 reference statements)
4
52
0
2
Order By: Relevance
“…Visceral fat is strongly related to the development of cardiovascular diseases [17] and, generally, an increase in visceral fat is accompanied by overall weight gain. In some cases visceral fat can be increased without overall weight gain.…”
Section: Discussionmentioning
confidence: 99%
“…Visceral fat is strongly related to the development of cardiovascular diseases [17] and, generally, an increase in visceral fat is accompanied by overall weight gain. In some cases visceral fat can be increased without overall weight gain.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, ectopic deposition of fat e.g. in skeletal muscle or liver is per se associated with an increased metabolic risk (Shimabukuro et al, 2013). This is best exemplified in patients suffering from lipodystrophy who are unable to store fat in white adipose tissue.…”
Section: Adipose Tissue and Adipokinesmentioning
confidence: 99%
“…A number of recent studies demonstrated that PAT affect the functions of PAT-adjacent vasculature and contribute to vascular remodeling. 46,47 Adipocytes originally differentiate from adipocyte progenitors and are related to the remodeling of adipose tissues under certain local and general conditions. MSCs residing in the perivascular region depots form and give rise to resident adipocyte progenitors.…”
Section: Mpcs Exhibit Bipotential Pluripotencymentioning
confidence: 99%